(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
Public service is basically is an action or advantage that offered to another part and basically has no form that can be feel or experienced and that means is service is some kind of product that makes this product is unreal and cant be feel. So the government have to make sure for building trust to public that of course needed effort to make it that happen and need extra effort for gaining public trust to the government and for making the public feel that they got the best service from government because as citizen they have a rights to got the best public service, management information system itself is a one of the factor or support that can make public servie become more efficient and effective because the system use technology as one of the part of the system management information system itself is activity that provide information Keyword : Information System,Management,Public Service